Interpretation of Freedom of Contract to the Decision of the Constitutional Court of the Republic of Indonesia - Sultan Alwan (Khairun Law Journal, 2018)
The principle of freedom of contract is a principle in the treaty law that cannot be understood absolutely for anyone who is involved in an agreement. In order to make a binding in the contract/agreement, the parties should still take into account the essence of the equilibrium value of the parties to an agreement to avoid the existence of contracts/standard agreements that would precisely eliminate the value of justice for the right that should be obtained for one of the contracting parties. for example, contracts/labour agreements made between employers and workers/labourers in the case of termination of employment due to the existence of inter-worker/labourer marriage ropes in one company as regulated in Article 153 paragraph (1) letter f of Law of the Republic of Indonesia Number 13 Year 2003 concerning Manpower. For the applicant a judicial review of the provisions of the article in the Constitutional Court of the Republic of Indonesia, to assess the provisions of that article is of constitutional harm if such provisions continue. The Constitutional Court of the Republic of Indonesia in its legal consideration of Decision Number 13/PUU-XV/2017 considers the principle of freedom of contract in the context of the article whose judicial review is no longer relevantbecause it does not meet the value of the balance in the process of contracting/agreement and eliminating the justice of one of the parties involved in the contract.